2010
DOI: 10.1103/physrevb.82.020405
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic cagelikeFe4O6cluster: Structure determination from infrared dissociation spectroscopy

Abstract: Cationic iron-oxide clusters of several sizes and stoichiometries have been synthesized and studied isolated in the gas phase. Vibrational spectra of the clusters have been measured using resonant IR- With the continuous trend of increasing the density of electronic devices, novel concepts are needed to answer the increasing technical problems. Many of these concepts require the creation of dedicated nanosized building blocks with well understood and a priori designed properties. For application in quantum com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
2
21
2
Order By: Relevance
“…Therefore, comparison with an experimental method to confirm the theoretical findings is essential. In this work, we combine previously reported experimental vibration spectra 30 …”
Section: 29mentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, comparison with an experimental method to confirm the theoretical findings is essential. In this work, we combine previously reported experimental vibration spectra 30 …”
Section: 29mentioning
confidence: 70%
“…Especially for the B3LYP functional it has been shown that this results in good agreement between the geometric structure and vibrational spectra for clusters. 28,30,37 However, hybrid functionals are quite computationally expensive compared to LDA and GGA functionals. Therefore, in the genetic algorithm we employ the GGA+U method to take into account that FeO clusters are strongly interacting systems.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This highly-symmetric structure is also common to other transition metal oxides such as Fe4O6 + , Sc4O6 + , and Nb4O10 + . [39][40][41] The bond dissociation energy of O2 from Mn4O6 + was calculated from the energy difference between Mn4O6 + and Mn4O4 + to be 1.8 eV. As Mn4O4 + was reported to have the ring structure, where Mn and O atoms were alternatingly-bridged, rupturing the bonds of bridging oxygen from Mn4O6 + was considered to require higher energy.…”
Section: Structures Of Mn4om +mentioning
confidence: 99%
“…However, several spectroscopic techniques have been developed which, in combination with density functional theoretic calculations, allow us to obtain the plausible geometric arrangement of the cluster. Examples are photoelectron spectroscopyi (PES), 16−19 infrared multiple photon dissociation spectroscopy (IR-MPD), 3,20,21 ion mobility spectrometry (IMS), 22,23 reactivity with CO, 24,25 and collisioninduced dissociation. 26−28 Recently, the fragmentation patterns of cobalt oxide clusters observed in mass spectrometry of jets of clusters produced by laser ablation 29,30 were rationalized by Aguilera-del Toro et al by means of density functional theoretic calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Kirilyuk et al carried out IR-MPD experiments for cationic Fe oxide clusters of several sizes and stoichometries. 21 Comparing with density functional theory (DFT) calculations of the vibrational spectrum allowed them to determine the putative spin magnetic configuration of certain clusters. Ota et al studied Co oxide clusters by means of IMS.…”
Section: Introductionmentioning
confidence: 99%